Early time-related course of image findings in postmortem MRI: Typical findings and observer agreement in a porcine model. (September 2017) - Henes, Frank Oliver; Regier, Marc; Bannas, Peter; Henker, Marlen; Heinemann, Axel; Sperhake, Jan; Begemann, Philipp G.C.; Adam, Gerhard; Groth, Michael
Highlights: This study evaluates temporal evolution of fluid and gas accumulation in postmortem MRI in a porcine model. We found excellent intra- and interobserver agreement for postmortem MR imaging findings. Development of pulmonary and hepatic fluid collections shows a concordant time-related appearance in a porcine model. Time-related imaging findings in MRI might be supportive for the retrospective determination of time of death. Abstract: Purpose: To assess early time-related image findings in postmortem magnetic resonance imaging (MRI) and to evaluate observer agreement in a porcine model. Material and Methods: Three pigs were examined by MRI at 15 different time points in the first 36 h after death. Two observers independently recorded the postmortem interval (PMI) to the appearance of fluid collection (pleural space, interlobar and interlobular pulmonary fissures and hepatic interlobar fissures), gas accumulation (intrahepatic and intracardial) and blood clotting (aorta and intrahepatic venous vessels). Cohen's Kappa statistics and intraclass correlation coefficient (ICC) were used to evaluate intra- and interobserver agreement. Results: Intrahepatic gas was evident after 12, 17 and 30 h. Also, intracardiac gas was present in all animals. However, no chronological appearance has been observed. Blood clotting in the hepatic vein was observed within 3 min, aortic clotting with a delay of 2–12 h after death. Interlobular pulmonary fluid (median PMI: 2 h, range 2–2 h), pleural effusion (median PMI: 10.5 h, range 9-12 h) and hepatic interlobar fissure fluid (median PMI: 11.5 h, range 11–12 h) displayed a chronological appearance pattern. Qualitative and quantitative detection of most postmortem findings showed excellent intra- and interobserver agreement with Kappa values > 0.8 or ICC > 0.75. Conclusion: Pulmonary and hepatic fissural fluid collection as well as intravasal gas accumulation are early time-related image findings in postmortem MRI. The chronological appearance of these findings can be assessed with excellent observer agreement in a porcine model.